Adaptation Strategy of Migrant Crew on Taiwanese Fishing Vessels - Nur Cholik Widyan Saputra; Margaretha Hanit (Publikasi Indonesia, 2024)
This study aims to analyse the adaptation strategies used by migrant crew members on Taiwanese fishing vessels in facing the risks they face. The research's risks include heavy workloads, hazardous work environments, health, and forced labour exploitation. The research method used is a qualitative analysis using primary data from interviews with seven resource persons who are migrant crew members on Taiwanese fishing boats. The study results show that migrant crew members use various adaptation strategies to deal with the risks they face on fishing boats. These adaptation strategies include a more effective division of labour, the use of better technology or equipment to reduce physical burdens, joining a community of fellow migrant workers, and the fight for decent work rights. In addition, migrant crew members also use an adaptation strategy from the beginning of recruitment by choosing the departure process through the official route. This research makes an essential contribution to understanding how migrant crew members cope with the risks they face on Taiwanese fishing vessels. The practical implications of this study are the importance of paying attention to the welfare and work rights of migrant crew members and expanding understanding of the importance of adaptation strategies in increasing their resilience in often challenging and high-risk work environments.